Impact of oral palonosetron in improving quality of life as compared to other oral 5-HT3 antagonists in delayed chemotherapy induced nausea and vomiting in patients of head and neck cancer - Khare, Anubhuti; Mandloi, Varsha; Shrivastava, Abhishek; Shrivastava, Arun Kumar; Wadagbalkar, Prashant; Kumar, Akhilesh (International Journal of Basic & Clinical Pharmacology, 2019)
Background: Chemotherapy induced nausea and vomiting (CINV) remains one of the most common and debilitating complications of highly emetogenic chemotherapy (HEC). This study was undertaken to evaluate palanosetron against other 5-HT3 receptor antagonists in preventing delayed CINV with the aim of achieving complete response (CR) and improving quality of life (QoL). Methods: This was a prospective, observational study conducted on 75 histopathologically proven patients of squamous cell carcinoma of Head and Neck (H&N), who came to the Department of Radiation Oncology, Gandhi Medical College and Hamidia Hospital, Bhopal from January to December 2015. Standard protocol based chemotherapy containing highly emetogenic cisplatin based chemotherapy was administered to all the patients. For prevention of delayed chemotherapy induced nausea and vomiting all patients were prescribed oral 5-HT3 antagonists. Oral Ondansetron 4mg TDS was given to cohort 1, oral Granisetron 1 mg BD to cohort2 and oral Palanosetron 0.5mg OD was given to cohort 3. They were graded as complete response when they did not have complains of nausea and vomiting. Results: In Ondansetron, Granisetron and in Palanosetron cohort 29%, 53% and 98% patients had complete response. Conclusions: Palanosetron appears superior. Our study was conducted on handfull of patients and compared palanosetron against only two 5-HT3 receptor antagonists, so a larger study is suggested to establish the efficacy and better response of palanosetron.